TEACHING HOW TO WRITE A RESEARCH PAPER - Hatziolou, Elizabeth; Sofiou, Stamatia (The Modern Higher Education Review, 2020)
The article aims at offering help to lecturers that want to teach their students how to write an acceptable research paper. As grammar and/or syntax can contribute to writing correct sentences but cannot aid students in developing a well-written research paper, lecturers should teach their students how to acquire important skills that will help them to compose a correct research paper. Such skills involve the acquisition of the ability to develop paragraphs, a series of sentences developing one topic, and the composition of a paper through a series of paragraphs that develop several related topics. Paragraphs need to include unity, coherence, transition, reasons – to accept the arguments in the research paper – and some examples in order to give the reasons in the research paper more validity. While long paragraphs can make the reader tired, many short paragraphs can become monotonous and boring. In other words, the length of paragraphs in a research paper is important. So is a closing, a summary sentence for the end of the development of the topic sentence, signalling that the writer is ready to move on to another idea and lists of details, like illustrations, examples, contrast, comparison, cause and effect and a combination of methods. The purpose of the research paper is considered to be of utmost importance and corresponds to one of the four main types of writing, including explanation, argument or mixtures, depending on the title and the central idea. Limiting the subject by providing an outline is helpful in organizing the student’s thoughts and avoiding overlapping. The inclusion of citations and a bibliography are obligatory for diligence in fulfilling the requirements of the university or college.